2022
DOI: 10.3389/fpubh.2022.858552
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Women's Empowerment in a Community-Based Human Papillomavirus Self-Sampling Social Entrepreneurship Program (Hope Project) in Peru: A Mixed-Method Study

Abstract: IntroductionUnderstanding community women's relational and financial empowerment in social entrepreneurship could be the key to scaling up community-based human papillomavirus (HPV) self-sampling programs in low- and middle-income countries. The Hope Project, social entrepreneurship in Peru, trains women (Hope Ladies) to promote HPV self-sampling among other women in their communities. This study aims to evaluate the Hope Ladies' relational and financial empowerment after participating in the program.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…User respondents have more donkeys and goats, which shows a significant difference because user respondents can access grass and other fodder for their livestock feed from the rehabilitated land. The result is in line with literature which indicated that understanding women's empowerment regarding the economic and social dimensions could be the key to scaling up community-based natural resource management programs in low-and middle-income countries like Ethiopia (Namubiru-Mwaura 2021; Shin et al 2022).…”
Section: Demographic and Land Use Characteristics Of Householdssupporting
confidence: 87%
“…User respondents have more donkeys and goats, which shows a significant difference because user respondents can access grass and other fodder for their livestock feed from the rehabilitated land. The result is in line with literature which indicated that understanding women's empowerment regarding the economic and social dimensions could be the key to scaling up community-based natural resource management programs in low-and middle-income countries like Ethiopia (Namubiru-Mwaura 2021; Shin et al 2022).…”
Section: Demographic and Land Use Characteristics Of Householdssupporting
confidence: 87%
“…This approach is considered as a source of overcoming issues of common method biasness ( Podsakoff et al, 2003 ). Self-sampling approach was used to access the students who were willing to be participant of the study ( Shin et al, 2022 ). At first point of time 487 students participated and filled their responses for entrepreneurial self-efficacy and family support.…”
Section: Methodsmentioning
confidence: 99%